2012
DOI: 10.1093/nar/gks1254
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 frameshift efficiency is primarily determined by the stability of base pairs positioned at the mRNA entrance channel of the ribosome

Abstract: The human immunodeficiency virus (HIV) requires a programmed −1 ribosomal frameshift for Pol gene expression. The HIV frameshift site consists of a heptanucleotide slippery sequence (UUUUUUA) followed by a spacer region and a downstream RNA stem–loop structure. Here we investigate the role of the RNA structure in promoting the −1 frameshift. The stem–loop was systematically altered to decouple the contributions of local and overall thermodynamic stability towards frameshift efficiency. No correlation between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
94
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 83 publications
24
94
1
Order By: Relevance
“…2E and F). These results are highly similar to previously described in vitro data (6). As expected, no frameshifting was detected when the slippery site was mutated to a nonslippery sequence ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…2E and F). These results are highly similar to previously described in vitro data (6). As expected, no frameshifting was detected when the slippery site was mutated to a nonslippery sequence ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with this idea, Brakier-Gingras and coworkers found that decreased translation initiation of HIV-1 mRNA resulted in increased frameshifting (13). Additionally, we found that disruption of the genomic secondary structure by mutagenesis led to increased frameshifting in vitro (6,14). SHAPE (selective 2-hydroxyl acylation analyzed by primer extension) data indicate that the genomic secondary structure is remodeled during translation, as regions of the RNA are unfolded and sequestered by the ribosome (14).…”
supporting
confidence: 86%
See 3 more Smart Citations